THE INFLUENCE OF SOCIO-ECONOMIC FACTORS ON THE DEVELOPMENT OF RESIDENTIAL MORTGAGE LENDING (CASE STUDY OF THE ALTAI TERRITORY) - N. I. Glotova; T. E. Fasenko (Финансы: теория и практика)
Nowadays the residential mortgage lending is a matter of great importance for the socio-economic development of Russia in the context of providing the majority of people with owner-occupied homes. The problem can be solved by increasing the availability of housing in which case the state support can be hardly overestimated. The paper analyzes the conditions for the organization of the mortgage lending system at the federal and regional levels (by the case study of the Altai Territory). The research findings made it possible to identify the main factors hampering the mortgage development: limited effective demand of the population, high housing prices, low volumes of new housing supply in federal subjects of the Russian Federation, inability to confirm incomes, economic instability, high interest rates, imperfect legislation. Taking into account the obtained results, the authors propose measures aimed at further development of the residential mortgage lending system. Besides, there is a need to raise the awareness of potential borrowers about the possibilities of mortgage programs through awareness-raising activity, publication of interviews with bank executives and the release of methodological literature. The findings concerning the influence of socio-economic factors on the development of the mortgage lending system can be used in the practice of credit institutions to increase the availability of residential mortgage loans.